Solid state 31phosphorus nuclear magnetic resonance of iron-, manganese-, and copper-containing synthetic hydroxyapatites - Sutter, B (Soil Science Society of America journal. Soil Science Society of America, 2002)
The incorporation of micronutrients into synthetic hydroxyapatite (SHA) is proposed for slow release of these nutrients to crops in the National Aeronautics and Space Administration's (NASA's) Advanced Life Support (ALS) program for Lunar or Martian outposts. Solid state 31P nuclear magnetic resonance (NMR) was utilized to examine the paramagnetic effects of Fe3+, Mn2+, and Cu2+ to determine if they were incorporated into the SHA structure. Separate Fe3+, Mn2+, and Cu2+ containing SHA materials along with a transition metal free SHA (pure-SHA) were synthesized using a precipitation method. The proximity (<1 nm) of the transition metals to the 31P nuclei of SHA were apparent when comparing the integrated 31P signal intensities of the pure-SHA (87 arbitrary units g-1) with the Fe-, Mn-, and Cu-SHA materials (37-71 arbitrary units g-1). The lower integrated 31P signal intensities of the Fe-, Mn-, and Cu-SHA materials relative to the pure-SHA suggested that Fe3+, Mn2+, and Cu2+ were incorporated in the SHA structure. Further support for Fe3+, Mn2+, and Cu2+ incorporation was demonstrated by the reduced spin-lattice relaxation constants of the Fe-, Mn-, and Cu-SHA materials (T'=0.075-0.434s) relative to pure-SHA (T1=58.4s). Inversion recovery spectra indicated that Fe3+, Mn2+, and Cu2+ were not homogeneously distributed about the 31P nuclei in the SHA structure. Extraction with diethylene-triamine-penta-acetic acid (DTPA) suggested that between 50 and 80% of the total starting metal concentrations were incorporated in the SHA structure. Iron-, Mn-, and Cu-containing SHA are potential slow release sources of Fe, Mn, and Cu in the ALS cropping system